Intersection between Administrative Law and Private Law on Environmental Law Litigation in Indonesia Legal System - Julianto, Riki; Arifin, Ridwan (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper delves into the complex interplay between administrative and private law in environmental litigation within Indonesia's legal framework. Indonesia, rich in natural resources, faces pressing environmental challenges due to rapid industrialization and urbanization. Consequently, disputes often arise over environmental conservation, resource extraction, and pollution control, necessitating legal action to uphold environmental integrity. Administrative law governs governmental bodies responsible for environmental regulation, dictating procedures for permits, inspections, and sanctions. Conversely, private law regulates relationships between individuals and entities, encompassing tort liability, contractual obligations, and property rights. In environmental litigation, these legal domains intersect as plaintiffs seek remedies for harm caused by both public and private actors. The paper examines significant cases where administrative law intersects with private law doctrines, analyzing how administrative decisions may lead to civil claims under negligence, nuisance, or strict liability theories. It also explores the role of public interest litigation and citizen enforcement mechanisms in ensuring government accountability for environmental stewardship. Additionally, it evaluates the challenges and opportunities in navigating the convergence of administrative and private law, including issues of standing, jurisdiction, evidence, and remedies. Emphasizing judicial interpretation and legal harmonization, the paper underscores the symbiotic relationship between these legal realms in Indonesia's environmental litigation landscape. By shedding light on this intersection, it contributes to understanding environmental governance and access to justice while offering insights into global environmental law reconciling public and private interests.